A compatible standard policy measure to tackle solar photovoltaic waste in Indian scenario. (March 2020) - Sheoran, Manisha; Sharma, Susheela; Kumar, Pancham
Abstract: Expeditious evolution of solar photovoltaic industry has triggered transformation in energy sector across the world. After the concluded durability of the PV panels amount of junk originates. This junk is directed into the category of solid waste. With the increasing solar power plant installations in India the amount of waste to be accumulated in the nearby years to come will be a matter of grave concern. Hasty action should be taken by the Indian policy makers and other non-governmental agencies to process the solar photovoltaic recycling policies at commercial level in an economically sustainable manner. This paper inspects the prospective requisite of PV reprocessing legislation by investigating the current reprocessing arrangements of the commercialized first and second generation solar PV materials. Emphasis is also laid on the hazardous effects of the waste on human body. Quantity of reclaimed material is considered and its economic importance is analysed. Architectural liability is put at the utmost front for curbing out the havoc to be created by piling up of the junk photovoltaic materials through economically feasible policy framework. Through this article effective solar PV reclaiming policy framework is proposed for the Indian government which will foster new socio-economic, environmental and employment opportunities.